Evaluating the feasibility and the potential efficacy of e-learning-based speech therapy (EST) as a web application for speech training in dysarthric patients with Parkinson's disease: a case study - Beijer, Lilian J; Rietveld, Toni C M; Hoskam, Vera; Geurts, Alexander C H; de Swart, Bert J M (Telemedicine journal and e-health, 2010)
As a Web application for speech training, e-learning-based speech therapy (EST) is assumed to have potential for neurological patients who aim at independent speech training in their home environment. This article reports a case study of a patient with dysarthric speech due to Parkinson's disease (PD) who enrolled in a 4-week intensive speech training through EST. The primary goal was to investigate the feasibility and the potential efficacy of EST as a Web application for speech training in dysarthric patients with PD. The participant used EST, following a speech training program containing parts of the pitch limiting voice treatment for patients with PD. The feasibility of EST for independent speech training in the home environment was verified through a questionnaire. The questionnaire addressed the participant's individual experiences with EST as well as the extent of satisfaction with technological features of EST, the content of the speech training, and the suitability of the home training environment. The potential efficacy of EST as a device to improve speech intelligibility was investigated using a repeated measures with randomized blocks design. The proportion of correct orthographic transcriptions of semantically unpredictable sentences as well as ratings of perceived intelligibility on a 10-point scale were used as measures for speech intelligibility. Outcomes of the questionnaire resulted in recommendations to enhance EST feasibility. Speech intelligibility, as measured by transcription scores, improved significantly after EST training. This improvement was maintained for 2 weeks after completing the EST training, whereas considerably lower scores were observed after 11 weeks without training. Subjective ratings of intelligibility did not show significant differences across time. The results of this case study confirm the potential of EST for patients with PD.